Macroalgae reduces survival of nursery‐reared Acropora corals in the Florida reef tract. Issue 3 (12th September 2017) - van Woesik, Robert; Ripple, Kayla; Miller, Steven L.
Abstract : Recent declines in coral populations along the Florida reef tract have prompted the establishment of coral restoration programs which raise coral species, such as the threatened Acropora cervicornis, in nurseries ready for outplanting. Large numbers of nursery‐reared coral colonies have been outplanted along the Florida reef tract in recent years, yet few studies have characterized benthic habitats that are considered optimal for colony survival. In 2016, we surveyed 23 A. cervicornis restoration sites, located at six different reefs in the upper Florida Keys. We examined the condition of the outplanted corals and quantified the benthic assemblages adjacent to the outplanted coral colonies. We found that where A. cervicornis survived for more than 1 year, the substrate significantly supported less brown macroalgae of the genus Dictyota than at sites where A. cervicornis had died. Coral survival was highest at sites with less than 15% Dictyota cover. These results suggest that the habitat conditions that supported Dictyota spp. were not conducive to A. cervicornis growth and survival. Restoration practitioners should avoid attaching nursery‐raised corals to substrate with Dictyota spp. cover greater than 15%.